2003
DOI: 10.2136/sssaj2003.1319
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistivity Imaging for Detecting Soil Cracking at the Centimetric Scale

Abstract: soil water content. Mackie-Dawson et al. (1989) studied the evolution of the cracking system in the first 10 cm Electrical resistivity measurements at high resolution (1.5-cm elecof soil by using vertical image analysis. They observed trode spacing) were performed to detect, from the soil surface, small cracks developing within the soil. We recorded a vertical electrical significant soil structural changes during an annual cycle pseudo-section in a decimetric undisturbed homogenous soil block of drying and wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 27 publications
2
70
0
1
Order By: Relevance
“…This enabled the detection of badger burrows and the study of their network as demonstrated by Butler et al (1994). This also enabled the study of the crack opening at the centimetric scale by Samouelian et al (2003). Table 1 : Typical ranges of electrical resistivities of earth materials (after modified Palacky, 1987) The porosity can be obtained for the electrical property via the Archie's law, which for a saturated soil without clay is written as :…”
Section: Nature and Arrangement Of Solid Constituentsmentioning
confidence: 99%
“…This enabled the detection of badger burrows and the study of their network as demonstrated by Butler et al (1994). This also enabled the study of the crack opening at the centimetric scale by Samouelian et al (2003). Table 1 : Typical ranges of electrical resistivities of earth materials (after modified Palacky, 1987) The porosity can be obtained for the electrical property via the Archie's law, which for a saturated soil without clay is written as :…”
Section: Nature and Arrangement Of Solid Constituentsmentioning
confidence: 99%
“…In other studies, loose soil was associated with values around 50 Ohm m, whereas soil cracks produced large peaks in resistivity (Seger et al, 2009). The high sensitivity of resistivity to even small voids has also been documented by Samouelian et al (2003), who detected soil cracks at the centimetre scale with a miniaturized resistivity tomography setting. ERT is also sensitive enough to soil structure to detect the effect of different tillage systems on soils, possibly due to different aggregate dimensions (Basso et al, 2010).…”
Section: Resultsmentioning
confidence: 63%
“…Resistivity measurements were initially introduced in agriculture for measuring soil salinity. Over the last decade resistivity has been extensively used to characterize soil variability and system dynamics at several scales from centimetres to landscapes (Basso et al, 2010;Besson et al, 2010;Samouelian et al, 2003), thanks to its reliability, ease of measurement, and the correlation with several soil properties such as texture, bulk density and water content. The potential of ERT in horticulture has not been exploited yet.…”
Section: Introductionmentioning
confidence: 99%
“…Such transformation corresponds to mathematical inversions resultant from the application of the minimum-square smoothing method (Loke & Barker, 1996). According to Samouëlian et al (2003), inversion takes place in three stages: firstly, the field data constitute a pseudo-section; secondly, the data are calculated, and thirdly, adjustments are made between the measures and calculated data in order to reduce the differences between them, yielding a result closer to real (Fig. 3).…”
Section: Physiographic Settingmentioning
confidence: 99%